USM IN THE FINALS - MOHE ENTREPRENEURIAL AWARDS (MEA) 2016 INSTITUTIONAL AWARD FOR PUBLIC UNIVERSITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
KUALA LUMPUR, 27 January 2017 Universiti Sains Malaysia (USM) qualifies for the finals in the Institutional Award for Public University category at the MOHE Entrepreneurial Awards (MEA) 2016, held in Kuala Lumpur recently.